LjNRT2.3 plays a hierarchical role in the control of high affinity transport system for root nitrate acquisition in Lotus japonicus - Rogato, Alessandra; Valkov, Vladimir Totev; Chiurazzi, Maurizio (Frontiers in Plant Science, 2022)
Nitrate is a key mineral nutrient required for plant growth and development. Plants have evolved sophisticated mechanisms to respond to changes of nutritional availability in the surrounding environment and the optimization of root nitrate acquisition under nitrogen starvation is crucial to cope with unfavoured condition of growth. In this study we present a general description of the regulatory transcriptional and spatial profile of expression of the Lotus japonicus nitrate transporter NRT2 family. Furthermore, we report a phenotypic characterization of two independent Ljnrt2.3 knock out mutants indicating the involvement of the LjNRT2.3 gene in the root nitrate acquisition and lateral root elongation pathways occurring in response to N starvation conditions. We also report an epistatic relationship between LjNRT2.3 and LjNRT2.1 suggesting a combined mode of action of these two genes in order to optimize the Lotus response to a prolonged N starvation